The Toronto Extremity Salvage Score in Unoperated Controls: An Age, Gender, and Country Comparison. (13th September 2012) - Clayer, Mark; Doyle, Simon; Sangha, Nicole; Grimer, Robert
Abstract : The Toronto Extremity Salvage Score (TESS) is widely used for the functional assessment of patients following surgery for musculoskeletal tumours. The aim of this study was to determine if there are gender and/or age-specific changes, unrelated to surgery, that may influence this score and the appropriateness of the questions. The TESS for lower limb was carried out in two different countries to see if there was variation between them. There were no statistically significant differences between the scores obtained between the respondents from Australia or Britain either in total or between the corresponding age groups. There were statistically significant differences in the TESS obtained between age groups with a lower score at older age groups but there was no difference between the sexes. Patients in the age group 70+ were more likely to record activities as "not applicable" and also have a lower score. This study has shown that age is the major factor in determining the TESS in both an Australian and British populations of otherwise healthy people. As there were no differences between the two populations, it supports the TESS as an international scoring system. There may be also an argument for age-specific questions.